(untitled) (Journal of Biomedical Investigation, 2008)
The study was designed to assess the Red Blood Cell parameters in Nigerian women using oral contraceptives (Lo-Femenal). 50 women practicing the oral contraception method for varying length of time were recruited for the study. They comprise 22 women who had been on Lo-femenal for < 1 year 9 women who had been on Lo-femenal for 1 year and 19 women had been on Lo-femenal for > 1 year. Similarly 50 women not practicing contraception were recruited and served as control. Blood samples collected from all participants were used for the analysis of some haematological parameters using standard haematological techniques. The result showed that the Haematocrit, haemoglobin and red blood. cell count dropped significantly in the Lo-femenal users compared with non-users (p < 0.001). The drop in blood levels of these parameters was much profound in users of < 1 year duration. On the other hand, red cell indices (MCHC, MCV and MCH) were significantly raised in users compared with non-users (p<0.001). These elevations were more in users of < 1 year duration. Blood films from Lo[1]Femenal users predominantly showed mild macrocytosis and anisocytosis. The reversibility of haemoglobin and packed cell volume with time in women who initiate Lo-Femenal warrants further study.